Computer education and child: scan options - João Josué Silva Filho (Universidade Federal de Santa Catarina, 2003)
In this paper we present the result of part of the investigations conducted by researchers brought together around the theme "child - computer ", which since 1995 have been studying at the Center for Science Education of UFSC the pedagogical possibilities of insertion of the computer in child education.